CONTRASTIVITY OF 'MO' AS AN AFFIRMATION PARTICLE IN JAPANESE AND 'JUGA' AS ADVERB IN INDONESIAN - Raden Novitasari (WIDAI Japanese Journal, 2021)
The difference between Japanese and Indonesian is quite diverse, one of which is about 'mo' and 'juga‘. 'Mo' includes affirmation particles in Japanese and 'juga‘ includes adverbs in Indonesian. This study aims to compare the two linguistic elements by looking for similarities and differences. The Japanese theory used is the theory of the structure and meaning of the affirmation particle 'mo', while the Indonesian theory used is the theory of structure and the meaning of adverbs 'juga'. The results obtained from this study are 'mo' and 'juga' used in the form of equalization adding an element into other similar elements, can be attached to the class of nouns, noun phrases, verbs, and adjectives. The difference is that 'mo' is after the element it adds, while 'juga' is more flexible in position can be before or after the element it adds.